2013
DOI: 10.1007/s00455-013-9464-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Effortful Swallow and the Mendelsohn Maneuver on Tongue Pressure Production against the Hard Palate

Abstract: Although effortful swallow and the Mendelsohn maneuver are commonly used in dysphagia rehabilitation, little is known about their effects on tongue-palate pressure production. The purpose of this study was to investigate the effects of effortful swallow and the Mendelsohn maneuver on tongue pressure production. Fourteen healthy volunteers (10 men, 4 women; age range = 21-41 years) participated. Tongue pressures during dry swallow, water swallow, effortful swallow, and the Mendelsohn maneuver were measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…In addition, recent studies of the Mendelsohn maneuver, a technique which prolongs maximum elevation of the hyolaryngeal complex during swallowing, have reported increased opening of the upper esophageal sphincter and improved swallow coordination following treatment in stroke survivors with dysphagia [17]. Additional work incorporating healthy volunteers has documented increased tongue-palate contact pressure during application of this swallowing maneuver [18]. Finally, a simple jaw opening exercise has been shown to improve opening of the upper esophageal sphincter during swallowing [19].…”
Section: Examples Of Exercise Based Dysphagia Therapiesmentioning
confidence: 99%
“…In addition, recent studies of the Mendelsohn maneuver, a technique which prolongs maximum elevation of the hyolaryngeal complex during swallowing, have reported increased opening of the upper esophageal sphincter and improved swallow coordination following treatment in stroke survivors with dysphagia [17]. Additional work incorporating healthy volunteers has documented increased tongue-palate contact pressure during application of this swallowing maneuver [18]. Finally, a simple jaw opening exercise has been shown to improve opening of the upper esophageal sphincter during swallowing [19].…”
Section: Examples Of Exercise Based Dysphagia Therapiesmentioning
confidence: 99%
“…The posterior thrust of the tongue was said to be strongly related to residues in the vallecula, whereas shortening and constriction of the pharynx are related to residues in pyriformis sinus (Stokely et al, 2015). Pharyngeal strengthening exercise through effortful swallow is designed to increase the basic motion of the tongue to the posterior and also the pharyngeal wall movement to anterior so that, there will increase the pressure for pushing the bolus and then reduce pharynx residual (Fukuoka et al, 2013;Palmer et al, 2000). Movement of the bolus during swallowing depends on the synergistic action of the oropharyngeal propulsion and hypopharyngeal suction.…”
Section: Discussionmentioning
confidence: 99%
“…Contact that occurs between the anterior part of the tongue and the palate becomes an important part of tongue movement which will keep the bolus in the oral cavity and ensure proper transport of the bolus. Fukuoka et al (2013) evaluated the tongue pressure against the hard palate during swallowing with effortful swallow and obtained increased results when compared to normal swallowing without effortful swallow. Huckabee et al (2008) said that tongue pressure to the palate during effortful swallow will increase submental activation, orolingual pressure, and upper pharyngeal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decrease in tongue pressure observed in some cases of stroke was basically associated with the presence of dysphagia. Several studies in the literature have related the decrease in tongue pressure to the symptom of dysphagia (10,20,21,22,23,24) . The results of this study indicated that tongue pressure in the subjects affected with stroke could trigger dysphagia.…”
Section: Discussionmentioning
confidence: 99%